2020
DOI: 10.1101/2020.10.12.336834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

scATAC-Seq reveals epigenetic heterogeneity associated with an EMT-like process in male germline stem cells and its regulation by G9a

Abstract: Epithelial-mesenchymal transition (EMT) is a phenomenon in which epithelial cells acquire mesenchymal traits. It contributes to organogenesis and tissue homeostasis, as well as stem cell differentiation. Emerging evidence indicates that heterogeneous expression of EMT gene markers presents in sub-populations of germline stem cells (GSCs). However, the functional implications of such heterogeneity are largely elusive. Here, we unravelled an EMT-like process in GSCs by in vitro extracellular matrix (ECM) model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 106 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Assessment of enriched TFs and their cognate motifs identified several known cell type-specific regulators – including the nuclear receptors (NR4A1 and NR5A1) in Sertoli cells and Leydig cells, ESR2 in Leydig cells, MYOG in PTMs, and previously uncharacterized TFs as potential cell type-specific regulators ( Figure 2C ). For example, we found that ZEB1 and SNAI2 motifs were enriched in germ cells, indicating they may undergo mesenchymal-like transition in perinatal development ( Hammoud et al, 2015 ; Liao et al, 2020 ). DNA bound by TFs is protected from transposition by Tn5, which can be visualized by plotting the ‘footprint’ pattern of each TF as the local chromatin accessibility surrounding the motif midpoint.…”
Section: Resultsmentioning
confidence: 96%
“…Assessment of enriched TFs and their cognate motifs identified several known cell type-specific regulators – including the nuclear receptors (NR4A1 and NR5A1) in Sertoli cells and Leydig cells, ESR2 in Leydig cells, MYOG in PTMs, and previously uncharacterized TFs as potential cell type-specific regulators ( Figure 2C ). For example, we found that ZEB1 and SNAI2 motifs were enriched in germ cells, indicating they may undergo mesenchymal-like transition in perinatal development ( Hammoud et al, 2015 ; Liao et al, 2020 ). DNA bound by TFs is protected from transposition by Tn5, which can be visualized by plotting the ‘footprint’ pattern of each TF as the local chromatin accessibility surrounding the motif midpoint.…”
Section: Resultsmentioning
confidence: 96%
“…The interaction with ECM molecules may induce epithelial-to-mesenchymal transition (EMT) [ 37 , 38 ], which is a crucial cellular program that enables polarized epithelial cells to transition toward a mesenchymal phenotype with increased cellular motility [ 39 ]. EMT can be initiated by external signals, such as transforming growth factor (TGF)-β [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…While single cell transcriptomic profiling has enabled us to look at EMT from an individualistic perspective, the chromatin regulation of the transcriptional activity of EMT genes in concert with TFs is still largely uncharted at a single cell resolution. By using Assay for Transposase-Accessible Chromatin using sequencing (ATACseq) in single cells, germline stem cells (GSCs) have been clustered into epithelial-like and mesenchymal-like states that constitute into an EMT spectrum 101 .…”
Section: Heterogeneity and Dynamic Genome Organization Of Emtmentioning
confidence: 99%